2015
DOI: 10.4103/0301-4738.169784
|View full text |Cite
|
Sign up to set email alerts
|

Primary orbital neuroblastoma with intraocular extension

Abstract: Neuroblastoma is an undifferentiated malignancy of primitive neuroblasts. Neuroblastoma is among the most common solid tumors of childhood. Orbital neuroblastoma is typically a metastatic tumor. In this case report, we describe a 2-year-old child with a rapidly progressing orbital tumor. Computed tomography revealed an orbital mass lesion with extraocular and intraocular components. An incisional biopsy was done, and a histopathological examination showed features suggestive of neuroblastoma. Systemic workup i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Ophthalmic involvement occurs in due course of NB in 50% of cases [ 6 ]. However, the initial presentation of this tumor with ophthalmic manifestation is rare and few cases were described in the literature as case reports [ 7 - 8 ]. Its ocular manifestations include orbital mass causing proptosis, ecchymosis, Horner’s syndrome, papilledema, nystagmus, extraocular muscle palsy, ptosis, and retinal striae [ 2 - 3 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ophthalmic involvement occurs in due course of NB in 50% of cases [ 6 ]. However, the initial presentation of this tumor with ophthalmic manifestation is rare and few cases were described in the literature as case reports [ 7 - 8 ]. Its ocular manifestations include orbital mass causing proptosis, ecchymosis, Horner’s syndrome, papilledema, nystagmus, extraocular muscle palsy, ptosis, and retinal striae [ 2 - 3 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Belgaumi et al suggested high dose multi-agent chemotherapy in infants and children under the age of two for prevention of blindness as such groups have the best chance for resolution [ 13 ]. Vallinayagam et al also reported a case of a rapidly progressive primary orbital NB in a two-year-old patient with an excellent response after completion of three cycles of chemotherapy [ 8 ]. Lastly, the prognosis of NB in children is dependent on many factors such as age at diagnosis, disease stage, and histological grade with the highest survival rate found in children under the age of two.…”
Section: Discussionmentioning
confidence: 99%
“…In the last 2 malignancies, the consistency of the tumor is firmer than in the case of NBL. 28 The orbit may rarely be the primary locus of the NBL, 26,27,47,61,71 and in contrast to the disease arising from the adrenals, it is resistant to chemotherapy and radiotherapy even at a young age. Hence, extended surgical treatment is necessary, which leads to unilateral blindness.…”
Section: Discussionmentioning
confidence: 99%
“…FIGURE 2. The association between the mean age of the Neuroblastoma patients and ophthalmologic manifestation according to our analysis of 65 case reports and Musarella et al[8][9][10][12][13][14][16][17][18][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] HS indicates Horner syndrome; OMS, opsoclonus-myoclonus syndrome. *Statistical significance.…”
mentioning
confidence: 99%
“… 22 23 24 Neuroblastoma represents the second most common orbital tumor in children after RMS, and only 8% cases first present with an orbital lesion. 25 Orbital neuroblastoma in children commonly occurs due to metastasis with primary in the abdomen. IHC plays an important role in differentiating neuroblastoma from other small round cell tumors such as retinoblastoma, RMS, and lymphoma.…”
Section: Discussionmentioning
confidence: 99%